AN ANALYSIS OF CALCULATION OF THE STRESS-STRAIN STATE OF PIPELINE DURING PROVIDING ISOLATION AND LAYING WORKS OF PIPELINE CONSTRUCTION PROСESS - Запухляк, Василь Богданович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
It is proposed to apply the method of three moments at the calculation of the stress-strain state of pipeline during providing isolation and laying works of pipeline construction process by the combined method. The analysis of existent methods of calculation of the stress-strain state is provided. Comparison of results of calculation using base methods and method of three moments and done, corresponding conclusions are acquired.